(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This thesis studies the description and significance of juniper species found in the mountains of Uzbekistan. The research analyzes their ecological role and economic benefits. Juniper plays a crucial role in preserving the ecosystem.